2020
DOI: 10.1007/s00018-020-03526-7
|View full text |Cite|
|
Sign up to set email alerts
|

What microRNAs could tell us about the human X chromosome

Abstract: MicroRNAs (miRNA) are small-non coding RNAs endowed with great regulatory power, thus playing key roles not only in almost all physiological pathways, but also in the pathogenesis of several diseases. Surprisingly, genomic distribution analysis revealed the highest density of miRNA sequences on the X chromosome; this evolutionary conserved mammalian feature equips females with a larger miRNA machinery than males. However, miRNAs contribution to some X-related conditions, properties or functions is still poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 87 publications
2
45
0
3
Order By: Relevance
“…The miRNA expression profiles in first and third trimester have similar chromosome distributions, with expected peaks at chromosomes 14 and 19, as well as peaks at chromosome 1, the largest human chromosome and chromosome X, which has a higher density of miRNAs compared to autosomes. 61,62 The most highly expressed miRNA, hsa-miR-126-3p, was upregulated in third trimester, and was validated with qRT-PCR using an independent cohort. In a recent study comparing first and second trimester placenta, miR-126-3p was identified to be among the 10 most highly expressed miRNAs and identified in maternal plasma.…”
Section: Discussionmentioning
confidence: 94%
“…The miRNA expression profiles in first and third trimester have similar chromosome distributions, with expected peaks at chromosomes 14 and 19, as well as peaks at chromosome 1, the largest human chromosome and chromosome X, which has a higher density of miRNAs compared to autosomes. 61,62 The most highly expressed miRNA, hsa-miR-126-3p, was upregulated in third trimester, and was validated with qRT-PCR using an independent cohort. In a recent study comparing first and second trimester placenta, miR-126-3p was identified to be among the 10 most highly expressed miRNAs and identified in maternal plasma.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, estradiol has been proven to alter the expression of AGO, Drosha, and Dicer [21]. Surprisingly, despite genomic distribution analysis showing that the human X chromosome has a higher density of miRNAs compared to autosomes and the Y-chromosome [22,23], no literature data are currently available on sex-chromosome-related microRNAs implicated in NDs.…”
Section: Micrornas In the Brain: From Function To Gender Differencesmentioning
confidence: 99%
“…Therefore, discordance between cyst burden and renal function decline trajectories that could be explained by lower cyst growth and remarkably slowed kidney enlargement in this ADPKD patient. In the present study, it was hypothesized that coexisting ADPKD with masked KS and GS may have a synergistic effect on the stimulation of rapid evolution to ESRD, and their synergistic effect may be the result of regulation of multiple signaling pathways, including vascular disease [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] (see Figure 2 ).…”
Section: Discussionmentioning
confidence: 96%